Identification of Putative Elicitors From Plant Root Exudates Responsible for PsoR Activation in Plant-Beneficial Pseudomonas spp. by Docking and Molecular Dynamics Simulation Approaches to Decipher Plant–Microbe Interaction - Sati, Diksha; Joshi, Tushar; Pandey, Satish Chandra; Pande, Veni; Mathpal, Shalini; Chandra, Subhash; Samant, Mukesh (Frontiers in Plant Science, 2022)
Abstract Plants and rhizobacteria are co-existing since the beginning, but the exact mechanism of communication between them remains enigmatic. The PsoR protein of plant-beneficial Pseudomonas spp., a group of root-associated bacteria, is known to produce a range of anti-fungal and insecticidal secondary metabolites like 2,4-diacetyl phloroglucinol (DAPG), pyrrolnitrin, chitinase making them great biocontrol agents and thus helping in plant growth promotion. To better understand the inter-kingdom signaling between plants and Plant Growth Promoting Rhizobacteria (PGPR), the interaction of PsoR with various root exudates was investigated computationally. For this, we first modeled the PsoR protein and confirmed it using the Ramachandran plot. A total of 59 different low molecular weight phytochemicals, secreted as root exudates by plants, were identified by extensive text mining. They were virtually screened with the PsoR protein by molecular docking. Based on the lowest binding energy, ranging from -7.1 to -6.3 kcal mol-1, the top five exudates were chosen. To analyze the stability of the docked protein-ligand complex, a Molecular Dynamics (MD) simulation of 100 nanoseconds was done. Two root exudates, saponarin, and 2-benzoxazolinone (BOA) showed suitable binding with PsoR by forming hydrogen, hydrophobic, and Van der Waals interactions. To confirm the MD simulation results, RMSF, RG, SASA, and interaction energy were calculated. This computational study first time reports that saponarin and 2-BOA, predominantly present in the root exudates of barley and wheat respectively, demonstrate effective binding with the modeled PsoR protein and are likely of showing cross-kingdom interactions. Keywords: Plant growth-promoting rhizobacteria (PGPR), inter-kingdom signaling, PsoR, saponarin, 2-benzoxazolinone, Molecular Docking, Molecular Dynamic Simulation.